Response surface methodology application to fly ash based geopolymer synthesized by alkali fusion method - Demir, Funda; Derun, Emek Moroydor (ELSEVIER, 2019)
The rapid consumption of natural sources due to the technological development brings environmental and economic problems and makes usage of alternative sources obligatory. Fly ash is one of an industrial waste that can be used as alumina silicate source for geopolymerization. In this study, fly ash based geopolymer was synthesized by Alkali Fusion Method. The experimental set up was designed by Design Expert Trial 7 program and the optimum geopolymer synthesis conditions including additional Al2O3 ratio, curing temperature were determined by Central Composite Inscribed Design (CCI) Method. Also, ANOVA analysis and optimization were carried out. X-ray fluorescence spectrometer (XRF), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), Scanning electron microscope-Energy-dispersive X-ray (SEM-EDX) and Brunauer-Emmett-Teller (BET) analyzes were applied for the characterization studies of the raw materials and optimum geopolymer sample. According to optimization and analysis results, the optimum Al2O3 addition (%) and curing temperatures were determined as 70.76% and 36.75 degrees C, respectively. The degree of geopolymerization reaction for optimum geopolymer sample was found as 97%.
Keywords: Geopolymer; Fly ash; RSM method; Al2O3 addition; METAKAOLIN-BASED GEOPOLYMER; HEAVY-METAL ADSORPTION; COMPRESSIVE STRENGTH; DESIGN; OPTIMIZATION; Materials Science